Surgeons’ Ability to Predict the Extent of Surgery Prior to Cytoreductive Surgery with Hyperthermic Intraperitoneal Chemotherapy - Hentzen, Judith E. K. R. (Ann Surg Oncol, 2020)
BACKGROUND: The extent of surgery (ES) during cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS + HIPEC) is a well-known risk factor for major postoperative morbidity. Interestingly, the reliability of surgeons to predict the ES prior to CRS + HIPEC is unknown. METHODS: In this prospective, observational cohort study, five surgeons predicted the ES prior to surgery in all consecutive patients with peritoneal metastases (PM) who were scheduled for CRS + HIPEC between March 2018 and May 2019. After the preoperative work-up for CRS + HIPEC was completed, all surgeons independently predicted, for each individual patient, the resection or preservation of 22 different anatomical structures and the presence of a stoma post-HIPEC according to a standardized ES form. The actual ES during CRS + HIPEC was extracted from the surgical procedure report and compared with the predicted ES. Overall and individual positive (PPV) and negative predictive values (NPV) for each anatomical structure were calculated. RESULTS: One hundred and thirty-one ES forms were collected from 32 patients who successfully underwent CRS + HIPEC. The number of resections was predicted correctly 24 times (18.3%), overestimated 57 times (43.5%), and underestimated 50 times (38.2%). Overall PPVs for the different anatomical structures ranged between 33.3 and 87.8%. Overall, NPVs ranged between 54.9 and 100%, and an NPV > 90% was observed for 12 anatomical structures. CONCLUSIONS: Experienced surgeons seem to be able to better predict the anatomical structures that remain in situ after CRS + HIPEC, rather than predict the resections that were necessary to achieve a complete cytoreduction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1245/s10434-020-08237-8) contains supplementary material, which is available to authorized users.